Practicality of Mathematics Learning Media Using Applications PowToon - Yolanda, Nela Sari; Laia, Niscaya (JERIT: Journal of Educational Research and Innovation Technology, 2024)
Learning mathematics has criteria that not everyone can easily understand. Mathematical formulas that some people find difficult to understand make students bored while studying. Suitable learning media such as animation and pictures will make the process more enjoyable. This research aims to determine the practicality of mathematics learning media created using the PowToon application for class XI Clothing students at SMK Negeri 6 Padang. This research will reveal the level of practicality of using learning media using the PowToon application from both teachers and students after using this learning media in the learning process. The learning media that has been developed and the questionnaire sheets have previously been validated by validators. Based on the research results, it shows that the learning media that has been developed is practical as seen from the practicality test results obtained from teacher responses and student responses. The practicality test results obtained were 81.73% for teacher responses and 77.03% for student responses. From the practical results that have been carried out, the learning media is in the practical category, so it is suitable for use in the mathematics learning process.